(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This contribution is focused on the decision of the Joined Sections of the Court of Cassation on the divergent jurisprudence on questions involving claims for damages about wrongful birth and wrongful life, evidence and causation. The J. S. don’t admit in the Italian law system wrongful life suits if the illness is not directly caused by medical malpractice.